Implications of Software Platform Architecture and Documentation on Developer Productivity: A Case of the Malawi Point of Care EMR Software - Mkambankhani, Emmanuel; Manda, Tiwonge (Journal of Health Informatics in Africa, 2024)
Background and Purpose: Software platform architecture and documentation affect platform customisability, developer productivity, and third-party contributions. This study examines how the Malawi Point of Care Electronic Medical Records Software (PoC-EMRS) architecture and documentation shape the platform’s customisation, developer productivity, and third-party contributions. The Malawi PoC-EMRS, as the primary case of analysis, was compared to CommCare and DHIS2 as configurable software platforms. Theoretically, we draw on Generativity and the Boundary Resource Model (BRM). Generativity evaluates the overall capacity of an artefact to produce solutions, for diverse use cases. BRM was used to evaluate how owners of the PoC-EMRS facilitate ecosystem value co-creation through documentation and exposure of APIs. Methods: Primary and secondary data were collected through interviews, observations and document analysis. Both qualitative and quantitative data were analysed to find common themes. Results: Malawi PoC-EMRS is less configurable than DHIS2 and CommCare, necessitating more developer effort to support a variety of use cases. Though Malawi PoC-EMRS exposes boundary resources, it lacks incentives to attract third-party developers. Lack of or limited access to detailed documentation also negatively affects internal and third-party development productivity. Conclusions: We established that CommCare and DHIS2 have the following strengths. First, the platforms feature standardised interfaces that allow third parties to design, configure, and customise the platforms into solutions for a varied range of use cases. Second, CommCare and DHIS2 have comprehensive documentation that is accessible through online repositories, communities of practice and demo sandboxes. Applying the strengths of these platforms in the development of the Malawi PoC-EMRS is likely to boost developer productivity.